2003
DOI: 10.1109/tadvp.2003.817477
|View full text |Cite
|
Sign up to set email alerts
|

A simple finite-difference frequency-domain (FDFD) algorithm for analysis of switching noise in printed circuit boards and packages

Abstract: Simultaneous switching noise (SSN) compromises the integrity of the power distribution structure on multilayer printed circuit boards (PCB). Several methods have been used to investigate SSN. These methods ranged from simple lumped circuit models to full-wave (dynamic) three-dimensional Maxwell equations simulators. In this work, we present an efficient and simple finite-difference frequency-domain (FDFD) based algorithm that can simulate, with high accuracy, the capacity of a PCB board to introduce SSN. The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…2) Full-Wave Simulation of a Complete Structure: Full wave analysis of a complete EEBG structure consists of simulating the exact structure with all the possible details using a numeric finite-element or finite-difference (time or frequency) method [28]. This can be achieved either by writing specific codes for solving Maxwell's equations in EEBG structures or by using generic commercial tools.…”
Section: ) Direct Experimentationmentioning
confidence: 99%
“…2) Full-Wave Simulation of a Complete Structure: Full wave analysis of a complete EEBG structure consists of simulating the exact structure with all the possible details using a numeric finite-element or finite-difference (time or frequency) method [28]. This can be achieved either by writing specific codes for solving Maxwell's equations in EEBG structures or by using generic commercial tools.…”
Section: ) Direct Experimentationmentioning
confidence: 99%
“…Notice that any device connected to via C will experience a high-frequency noise component due to the outgoing quasiradial wave, in addition to the lower-frequency components arising from the bouncing back and forth of the waves as they retlect off the boundary. [5] This active device experiences a disturbance It is shown that traces and power plane structures in packages behave more like transmission lines with irnpedance and delay rather than lumped inductors. So the transmission line method (TLM) can be used to model power/ground plane pairs.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest method with easy implementation is based on the cavity model that has been discussed [5] and extended [6,7], becoming the foundation of this paper. Other frequency-domain techniques such as the method of moments (MoM) or FDFD method can be found in [8] and [9], respectively. This paper presents the analysis method and numerical results for the PCB power/ground plane structures based on the cavity model with different formulations, where the treatments are similar to the microstrip antennas [10,11] to include the effects of dielectric, conductor, and radiation losses.…”
Section: Introductionmentioning
confidence: 99%